Analisis Faktor-faktor yang Mempengaruhi Kinerja Keuangan Usaha Mikro Kecil dan Menengah (UMKM) di Kota Medan - Rima Octaviani; Rizqy Fadhlina Putri (Regress: Journal of Economics & Management, 2021)
Micro, small and medium enterprises have a major contribution to the national and regional economy, thus sustainable empowerment are constantly needed. This study aims to determine the effect of capital (X1), business age (X2), and credit loan (X3) on the performance of micro, small and medium enterprises (Y) in Medan City. 50 business managers were selected as the research sample based on the purposive sampling technique. Data were collected using questionnaire, and were analyzed by using Multiple linear regression analysis processed in the SPSS program. The results demonstrated that capital and credit loan had a significant effect on business performance (p < 0.05). On the other hand, business age had no significant effect on business performance (p > 0.05). These findings indicate that regardless of how long a business has been established, the main determinants of its performance are capital adequacy and the access to credit services. These two significant factors should be the priority in the program of small business empowerments by the government of Medan City or related agencies.